Continuous venovenous hemofiltration in the management of paraquat poisoning: A meta-analysis of randomized controlled trials. Issue 20 (May 2017) - Lin, Guodong; Long, Jianhai; Luo, Yuan; Wang, Yongan; Zewu, Qiu
Abstract: Background: Paraquat (PQ) poisoning is a widespread occurrence, especially in underdeveloped areas. The treatment of PQ poisoning has always been difficult, and there is currently no definite effective treatment. Continuous venovenous hemofiltration (CVVH) treatment for PQ poisoning has been widely used in clinical practice; however, its effect remains uncertain. Accordingly, the purpose of this meta-analysis was to evaluate the efficacy of CVVH in the treatment of PQ poisoning. Methods: We searched for relevant trials using PubMed, Embase, the Cochrane Library, and 3 Chinese databases, the Chinese BioMedical Literature Database, National Knowledge Infrastructure Database, and Wanfang Database. We included all qualified randomized controlled trials (RCTs) of CVVH treatment for patients with PQ poisoning. The primary outcome was mortality, while the secondary outcomes included the survival time and constituent ratios of death due to respiratory failure and circulatory failure. Results: Three RCTs involving 290 patients were included. The mortality rates of the intervention and control groups were 57.9% and 61.0%, respectively. Pooled analysis demonstrated no significant difference in mortality between the CVVH treatment and control groups (risk ratio [RR] 0.94, 95% confidence interval [CI]: 0.78–1.15, P = .56), with a low level of heterogeneity (X 2 = 1.75, I 2 = 0%). However, the CVVH group was associated with a longer survival time compared to the control group (weighted mean difference 1.73, 95% CI: 0.56–2.90, P = .004). Respiratory failure as the cause of death was more common in the CVVH group, as compared with the control group (RR 1.66, 95% CI: 1.24–2.23, P = .0008), whereas patients in the control group were more likely to die from circulatory failure than in the CVVH group (RR 0.56, 95% CI: 0.40–0.81, P = .002). Conclusion: Although CVVH treatment might not noticeably reduce mortality for patients with PQ poisoning, it can prolong the survival time of the patients and improve the stability of the circulatory system, thereby enabling further treatment. Abstract : Supplemental Digital Content is available in the text